High-performance fiber-blended seawater and sea sand concrete and preparation method thereof
By adding corrosion-resistant fibers and mineral blends to seawater sea sand concrete, a three-dimensional framework structure is formed, which solves the problem of low corrosion resistance of seawater sea sand concrete, and significantly improves the mechanical properties and durability of concrete.
Patent Information
- Application Number
- CN202411427672.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-18
AI Technical Summary
The existing seawater and sea sand concrete has low corrosion resistance, and traditional steel fibers are easily corroded by harmful halide ions, reducing the service life of concrete.
By adding corrosion-resistant polyvinyl alcohol fibers, basalt fibers and high-quality mineral blends, the corrosion resistance of concrete is improved, and a three-dimensional framework structure is formed to enhance the density and durability of concrete.
It significantly improves the compressive strength, tensile strength and freezing resistance of concrete, extends the service life of concrete, and reduces the cost of raw materials and reduces dependence on freshwater and river sand.
Smart Images

Figure BDA0005082625860000071 
Figure HDA0005082625870000011 
Figure HDA0005082625870000012
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete materials and relates to a high-performance mixed fiber seawater and sea sand concrete and a preparation method thereof. Background Art
[0002] With the rapid development of my country's national economy, the demand for infrastructure construction is gradually increasing. As the main material for civil engineering construction such as residential buildings, bridges and roads, and public infrastructure, the consumption of concrete is also increasing. As the core raw materials of concrete, the demand for fresh water and river sand is also increasing sharply. However, due to environmental and resource constraints, the sustainable mining of river sand is very limited. The contradiction between the insufficient supply of sand and gravel output and the increasing scarcity of resources has led to an urgent need for resources that can replace fresh water and river sand in construction projects. my country is rich in seawater sand resources. Most of the sea sand is medium sand and fine sand. Compared with river sand, it has low mud content, good particle shape, and uniform fineness. It is suitable for use as construction sand in buildings. If sea sand and seawater are applied to actual construction projects of offshore and inland projects, it can improve the current shortage of freshwater river sand resources in my country to a certain extent. Summary of the invention
[0003] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a high-performance mixed fiber seawater sand concrete and a preparation method thereof, and specifically to address the shortcomings of ordinary seawater sand concrete, such as low corrosion resistance and easy corrosion by harmful halide ions after adding traditional steel fibers, which reduces the service life of concrete. The purpose of the present invention is to improve the corrosion resistance by adding polyvinyl alcohol fibers, basalt fibers and high-quality mineral admixtures with strong corrosion resistance, and to provide a high-performance mixed fiber seawater sand concrete and a preparation method thereof. The present invention mixes the two types of fibers into concrete, which is conducive to exerting the "positive mixing effect" of the fibers. The addition of mineral admixtures can significantly improve the internal microstructure of seawater sand concrete and the pore structure of the interface transition zone, play a synergistic role with the fibers, enhance the density of the concrete matrix, hinder the migration channel of ions, and solve the problem of low service life of seawater sand concrete in actual use.
[0004] In order to solve the above technical problems, the present invention adopts the following technical solutions to achieve the above problems:
[0005] A high-performance fiber-blended seawater and sea sand concrete comprises the following raw materials: cement, fly ash, silica fume, coarse aggregate, sea sand, seawater, water reducing agent, polyvinyl alcohol fiber and basalt fiber.
[0006] The present invention also includes the following technical features:
[0007] Specifically, the following raw materials are included, calculated by mass: 133.43 to 139.14 parts of cement, 38.11 to 39.82 parts of fly ash, 19.04 to 19.87 parts of silica fume, 460.08 to 468.89 parts of coarse aggregate, 259.51 to 263.75 parts of sea sand, 68.57 to 87.80 parts of seawater, 0.27 to 0.35 parts of water reducing agent, 0.91 to 2.73 parts of polyvinyl alcohol fiber, and 2.56 to 7.68 parts of basalt fiber.
[0008] Specifically, the cement is silicate cement.
[0009] Specifically, the fly ash has a specific surface area of 1300m 2 / kg, water requirement is 105%, spherical particle content is 91%, fineness is 20% fly ash microspheres; the particle size of silica fume used is 3000 mesh, the ignition loss is 3.42%, and the specific surface area is 19.1m 2 / g.
[0010] Specifically, the basalt fiber is a short-cut basalt fiber with a single fiber diameter of 15 μm, a length of 12 mm, a tensile strength of 4500 MPa, an elastic modulus of 75 GPa, and a density of 2.56 g / cm 3 .
[0011] Specifically, the polyvinyl alcohol fiber has a monofilament diameter of 15.3 μm, a length of 12 mm, a tensile strength of 1830 MPa, an elastic modulus of 40 GPa, and a density of 1.29 g / cm 3 , the elongation at break is 7%.
[0012] Specifically, the fineness modulus of the sea sand is 2.4 and the apparent density is 2.5-2.7 g / cm 3 .
[0013] Specifically, the water reducer is a polycarboxylic acid water reducer with a solid content of 38.3% and a water reduction rate of 27%.
[0014] The method for preparing the high-performance fiber-blended seawater and sea sand concrete comprises the following steps:
[0015] s1, prepare seawater and mix the seawater and water reducing agent in proportion;
[0016] s2, add cement, fly ash, silica fume, coarse aggregate and sea sand into the concrete mixer and stir for 3-5 minutes to make the materials homogeneous;
[0017] s3, add seawater and water reducing agent mixture, stir for 2-4 minutes, until a fluid gel slurry is obtained;
[0018] s4, add polyvinyl alcohol fiber and basalt fiber while stirring. When a certain amount of fiber is added, uneven distribution will occur. At this time, slowly add seawater again. After adding seawater, the clumping problem is alleviated. Then continue to slowly add fiber, repeat the cycle until all the fiber and seawater are added, and then stir for 3-5 minutes.
[0019] s5, adding the concrete material into the mold twice, and vibrating the concrete on a high-frequency vibration table for 1 minute after each loading;
[0020] s6, and then perform standard curing to obtain the high-performance mixed fiber seawater and sea sand concrete.
[0021] Specifically, the high-frequency vibration frequency is ≥12000 times / min.
[0022] Compared with the prior art, the present invention has the following technical effects:
[0023] (1) High strength. The present invention adds fly ash, silica fume and other mineral admixtures to cement, which can effectively improve the internal structure of concrete. In addition, silica fume particles are much smaller than cement particles, which can further improve the density of hydration products and fill pores through internal micro-filling effect, thereby enhancing the durability and mechanical properties of concrete.
[0024] (2) Strong frost resistance. The present invention mixes and adds polyvinyl alcohol fiber and basalt fiber into the concrete matrix. When the two fibers are mixed, the basalt fiber can significantly improve the compressive strength and tensile strength of the concrete, and the PVA fiber enhances the crack resistance of the concrete. The two fibers complement each other and form a three-dimensional skeleton in the concrete matrix, which effectively wraps the aggregate. At the same time, the development of microcracks inside can be limited, and the ion transmission channel can be blocked. At the same time, the addition of fibers has an indirect air entrainment effect. Under the combined effect of increasing the density of the concrete with the mineral admixture, the frost resistance can be effectively improved, and the durability of the concrete can also be guaranteed.
[0025] (3) Low cost. The present invention uses seawater and sand as raw materials, which can be obtained locally in the eastern coastal areas and marine engineering, thus not only reducing the cost of raw materials, but also reducing the cost of transporting fresh water and river sand from inland. At the same time, the present invention does not use fresh water and river sand, which can reduce the further consumption of river sand and fresh water resources, avoid a series of problems caused by excessive exploitation of sand and gravel resources, protect the natural ecological environment, and is conducive to sustainable development.
[0026] (4) Process. The present invention combines the characteristics of seawater and sea sand, breaks through the traditional concrete design concept, and adopts homogeneous mixing technology, compaction technology, and frequency vibration technology to significantly reduce the macroscopic defects of concrete, fully improve the density of concrete, and improve the performance of seawater and sea sand concrete. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of the strengthening mechanism of mineral admixtures.
[0028] Figure 2 Schematic diagram of the crack resistance mechanism of hybrid fibers.
[0029] Figure 3 Schematic diagram of concrete hole structure.
[0030] Figure 4 Schematic diagram of the hydration product morphology. DETAILED DESCRIPTION
[0031] The present invention provides a high-performance mixed fiber seawater and sea sand concrete and a preparation method thereof, comprising the following raw materials: cement, fly ash, silica fume, coarse aggregate, sea sand, seawater, water reducing agent, polyvinyl alcohol fiber, and basalt fiber. Among them, polyvinyl alcohol fiber is a new type of high-strength synthetic fiber, which has the advantages of high elastic modulus, good acid and alkali resistance, and good bonding strength with the concrete matrix; basalt fiber is made by melting basalt stone at high temperature and then drawing it at high speed from a drawing plate. Basalt fiber has excellent performance, outstanding mechanical properties, stable chemical properties, good dispersibility and low moisture absorption rate; polyvinyl alcohol fiber and basalt fiber have strong corrosion resistance, which overcomes the disadvantage of easy corrosion of traditional steel fibers. Mixing the two fibers into concrete is beneficial to exerting the "positive mixing effect" of the fibers. Adding mixed fibers and mineral admixtures can significantly improve the internal microstructure of seawater and sea sand concrete and the pore structure of the interface transition zone, and play a synergistic role (such as Figure 1 , 2 ), enhance the density of the concrete matrix (such as Figure 3 ), blocking the migration channel of ions. Prolong the service life of seawater sand, so that it can be better used in actual projects to meet engineering needs.
[0032] The present invention adds mixed fibers and high-quality mineral admixtures to the concrete matrix, which can improve the density of the interface transition zone, shrink microcracks, reduce porosity and enhance the structural density of hydration products. In addition, due to the volcanic ash effect of the mineral admixture, a low-alkalinity calcium silicate hydrate gel (CSH) with high strength and excellent stability is generated (such as Figure 4 ), CSH gel improves the ion solidification ability of seawater and sea sand concrete, hinders the ion migration channel, which is equivalent to setting up multiple obstacles on the path of corrosive substances on the concrete matrix and internal steel bars, thereby delaying the transmission speed of corrosive substances in the matrix and the inflow of exudative corrosive substances, improving the anti-corrosion performance of the matrix and enhancing the service life of concrete in complex environments such as low temperature, freeze-thaw, and corrosion. It can reduce the impact of corrosive substances on the concrete matrix structure, and at the same time delay the erosion of corrosive substances on internal steel bars, thereby enhancing the service life of concrete.
[0033] The present invention mixes polyvinyl alcohol fiber, basalt fiber and high-quality mineral admixture into the seawater and sea sand concrete matrix, and the advantages of the two fibers are combined. On a macro level, a three-dimensional skeleton is formed inside, which can effectively wrap the aggregate, reduce the internal defects of the concrete and improve its mechanical properties. On a micro level, the "bridging effect" of the mixed fiber is exerted to inhibit the development of micro cracks, and the salt and frost resistance of the concrete can be effectively improved. At the same time, the added silica fume and fly ash produce a volcanic ash effect with Ca(OH)2 to generate a low-alkalinity hydrated calcium silicate gel (CSH) with high strength and excellent stability. The CSH gel improves the ion curing ability of the seawater and sea sand concrete, hinders the ion migration channel, and can further increase the density and durability of the concrete matrix. By using this invention, when untreated seawater and sea sand are used to make concrete, the erosion of the concrete matrix by harmful ions can be reduced. Moreover, since the particle size of the mineral admixture is smaller than that of cement, the density of the "three-dimensional skeleton" formed by the mixed fiber can be further improved through the filling effect, thereby achieving the synergistic effect of the fiber and the mineral admixture, thereby enhancing the internal microstructure and durability of the concrete, and being able to better adapt to complex environments such as low temperature, freeze-thaw, and corrosion, so that it can be applied to some inland coastal areas with relatively scarce resources and marine engineering.
[0034] Specific embodiments of the present invention are given below. It should be noted that the present invention is not limited to the following specific embodiments, and all equivalent changes made on the basis of the technical solution of this application fall within the protection scope of the present invention.
[0035] The cement in the embodiment of the present invention is PO42.5 silicate cement produced by Shijiazhuang Quzhai Cement Co., Ltd.; the fly ash is a cement with a specific surface area of 1300m 2 / kg, water requirement is 105%, spherical particle content is 91%, fineness is 20% fly ash microspheres; the particle size of silica fume used is 3000 mesh, the ignition loss is 3.42%, and the specific surface area is 19.1m 2 / g; the diameter of the polyvinyl alcohol fiber is 15.3μm, the length is 12mm, the tensile strength is 1830MPa, the elastic modulus is 40GPa, and the density is 1.29g / cm 3 , elongation at break is 7%; chopped basalt fiber, single fiber diameter 15μm, length 12mm, tensile strength 4500MPa, elastic modulus 75GPa, density 2.56g / cm 3 ; The water reducer is polycarboxylic acid water reducer with a solid content of 38.3% and a water reduction rate of 27%.
[0036] Embodiment 1:
[0037] The present embodiment provides a high-performance mixed fiber seawater and sea sand concrete and a preparation method, comprising the following components: 133.43 kg of silicate cement, 87.80 kg of seawater, 259.51 kg of sea sand, 460.08 kg of coarse aggregate, 0.27 kg of water reducer, 38.11 kg of fly ash, 19.04 kg of silica fume, 0.91 kg of polyvinyl alcohol fiber, and 5.12 kg of basalt fiber.
[0038] The preparation process is as follows:
[0039] (1) Prepare seawater and mix the seawater and water reducing agent in proportion to make them uniform;
[0040] (2) Add cement, fly ash, silica fume, coarse aggregate and sea sand into a concrete mixer and stir for 3-5 minutes to homogenize the materials;
[0041] (3) Add a portion of the seawater and water reducing agent mixture and stir for 2-4 minutes until a gelatinous slurry with a certain fluidity is obtained;
[0042] (4) Add polyvinyl alcohol fiber and basalt fiber while stirring. When a certain amount of fiber is added, uneven distribution will occur. At this time, slowly add seawater again. After adding seawater, the clumping problem is alleviated. Then continue to slowly add fiber, repeat the cycle until all fiber and seawater are added, and then stir for 3-5 minutes.
[0043] (5) Add concrete material into the mold twice. After each addition, place the concrete on a high-frequency vibration table and vibrate for 1 minute.
[0044] (6) After standard curing, high-performance fiber-blended seawater and sea sand concrete is obtained.
[0045] Embodiment 2:
[0046] The present embodiment provides a high-performance mixed fiber seawater and sea sand concrete and a preparation method, comprising the following components: 133.43 kg of silicate cement, 87.80 kg of seawater, 259.51 kg of sea sand, 460.08 kg of coarse aggregate, 0.27 kg of water reducer, 38.11 kg of fly ash, 19.04 kg of silica fume, 1.82 kg of polyvinyl alcohol fiber, and 2.56 kg of basalt fiber.
[0047] The preparation process is as follows:
[0048] (1) Prepare seawater and mix the seawater and water reducing agent in proportion to make them uniform;
[0049] (2) Add cement, fly ash, silica fume, coarse aggregate and sea sand into a concrete mixer and stir for 3-5 minutes to homogenize the materials;
[0050] (3) Add a portion of the seawater and water reducing agent mixture and stir for 2-4 minutes until a gelatinous slurry with a certain fluidity is obtained;
[0051] (4) Add polyvinyl alcohol fiber and basalt fiber while stirring. When a certain amount of fiber is added, uneven distribution will occur. At this time, slowly add seawater again. After adding seawater, the clumping problem is alleviated. Then continue to slowly add fiber, repeat the cycle until all fiber and seawater are added, and then stir for 3-5 minutes.
[0052] (5) Add concrete material into the mold twice. After each addition, place the concrete on a high-frequency vibration table and vibrate for 1 minute.
[0053] (6) After standard curing, high-performance fiber-blended seawater and sea sand concrete is obtained.
[0054] Embodiment 3:
[0055] The present embodiment provides a high-performance mixed fiber seawater and sea sand concrete and a preparation method, comprising the following components: 133.43 kg of silicate cement, 87.80 kg of seawater, 259.51 kg of sea sand, 460.08 kg of coarse aggregate, 0.27 kg of water reducer, 38.11 kg of fly ash, 19.04 kg of silica fume, 2.73 kg of polyvinyl alcohol fiber, and 2.56 kg of basalt fiber.
[0056] The preparation process is as follows:
[0057] (1) Prepare seawater and mix the seawater and water reducing agent in proportion to make them uniform;
[0058] (2) Add cement, fly ash, silica fume, coarse aggregate and sea sand into a concrete mixer and stir for 3-5 minutes to homogenize the materials;
[0059] (3) Add a portion of the seawater and water reducing agent mixture and stir for 2-4 minutes until a gelatinous slurry with a certain fluidity is obtained;
[0060] (4) Add polyvinyl alcohol fiber and basalt fiber while stirring. When a certain amount of fiber is added, uneven distribution will occur. At this time, slowly add seawater again. After adding seawater, the clumping problem is alleviated. Then continue to slowly add fiber, repeat the cycle until all fiber and seawater are added, and then stir for 3-5 minutes.
[0061] (5) Add concrete material into the mold twice. After each addition, place the concrete on a high-frequency vibration table and vibrate for 1 minute.
[0062] (6) After standard curing, high-performance fiber-blended seawater and sea sand concrete is obtained.
[0063] Comparative Example:
[0064] Ordinary seawater and sea sand concrete includes the following components: 190.61 kg of Portland cement, 87.80 kg of seawater, 259.18 kg of sea sand, 461.22 kg of coarse aggregate, and 0.87 kg of water reducing agent.
[0065] According to the "Concrete Physical and Mechanical Properties Test Method Standard" (GB / T500812019), "Fiber Concrete Test Method Standard" (CECS132009) and "Ordinary Concrete Long-term and Durability Test Method Standard" (2009), the relevant parameters of Examples 1 to 3 and the comparative example, including cube compressive strength, axial tensile strength, and mass loss rate after freezing and thawing, were measured. The results are shown in Table 1.
[0066] Table 1 Measurement results
[0067]
[0068] From the results in Table 1, it can be seen that compared with ordinary seawater sand concrete, the high-performance mixed fiber seawater sand concrete prepared by the present invention has a cubic compressive strength of more than 35MPa, an axial compressive strength of more than 28MPa, a mass loss rate after freezing and thawing less than that of ordinary seawater sand concrete, and a small loss of compressive strength after freezing and thawing. This shows that the present invention adds mixed fiber and high-quality mineral admixtures to seawater sand concrete, reduces the defects inside the concrete, improves the microstructure, and improves the mechanical properties and durability of the concrete.
[0069] It should be noted that the above embodiments all belong to the same inventive concept, and the description of each embodiment has its own focus. For matters that are not described in detail in some embodiments, reference may be made to the description in other embodiments.
[0070] The above embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention.
Claims
1. A high performance fiber-blended seawater and sea sand concrete, characterized in that: Including the following raw materials: cement, fly ash, silica fume, coarse aggregate, sea sand, sea water, water reducing agent, polyvinyl alcohol fiber, basalt fiber.
2. The high performance fiber-blended seawater and sea sand concrete according to claim 1, characterized in that: The following raw materials are included by mass: 133.43-139.14 parts of cement, 38.11-39.82 parts of fly ash, 19.04-19.87 parts of silica fume, 460.08-468.89 parts of coarse aggregate, 259.51-263.75 parts of sea sand, 68.57-87.80 parts of seawater, 0.27-0.35 parts of water reducer, 0.91-2.73 parts of polyvinyl alcohol fiber, and 2.56-7.68 parts of basalt fiber.
3. The high performance fiber-blended seawater and sea sand concrete according to claim 1, characterized in that: The cement is silicate cement.
4. The high performance fiber-blended seawater and sea sand concrete according to claim 1, characterized in that: The fly ash has a specific surface area of 1300m 2 / kg, water requirement is 105%, spherical particle content is 91%, fineness is 20% fly ash microspheres; the particle size of silica fume used is 3000 mesh, the ignition loss is 3.42%, and the specific surface area is 19.1m 2 / g.
5. The high performance fiber-blended seawater and sea sand concrete according to claim 1, characterized in that: The basalt fiber is a short-cut basalt fiber with a single-filament diameter of 15 μm, a length of 12 mm, a tensile strength of 4500 MPa, an elastic modulus of 75 GPa, and a density of 2.56 g / cm 3 .
6. The high performance fiber-blended seawater and sea sand concrete according to claim 1, characterized in that: The polyvinyl alcohol fiber has a monofilament diameter of 15.3 μm, a length of 12 mm, a tensile strength of 1830 MPa, an elastic modulus of 40 GPa, and a density of 1.29 g / cm 3 , the elongation at break is 7%.
7. The high performance fiber-blended seawater and sea sand concrete according to claim 1, characterized in that: The sea sand has a fineness modulus of 2.4 and an apparent density of 2.5-2.7 g / cm 3 .
8. The high performance fiber-blended seawater and sea sand concrete according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid water reducing agent with a solid content of 38.3% and a water reducing rate of 27%.
9. The method for preparing high performance mixed fiber seawater and sea sand concrete according to claim 1, characterized in that: The following steps are involved: s1, prepare seawater and mix the seawater and water reducing agent in proportion; s2, add cement, fly ash, silica fume, coarse aggregate and sea sand into the concrete mixer and stir for 3-5 minutes to make the materials homogeneous; s3, add seawater and water reducing agent mixture, stir for 2-4 minutes, until a fluid gel slurry is obtained; s4, add polyvinyl alcohol fiber and basalt fiber while stirring. When a certain amount of fiber is added, uneven distribution will occur. At this time, slowly add seawater again. After adding seawater, the clumping problem is alleviated. Then continue to slowly add fiber, repeat the cycle until all the fiber and seawater are added, and then stir for 3-5 minutes. s5, adding the concrete material into the mold twice, and vibrating the concrete on a high-frequency vibration table for 1 minute after each loading; s6, and then perform standard curing to obtain the high-performance mixed fiber seawater and sea sand concrete.
10. The method for preparing high performance fiber-blended seawater and sea sand concrete according to claim 9, characterized in that: The high-frequency vibration frequency is ≥12000 times / min.
Citation Information
Cited By
Construction method of fiber-reinforced high-performance seawater and sea sand concrete shrinkage prediction model
CN121096504A